Characterization of ZnMoO4 nanofibers synthesized by electrospinning-calcination combinations - Keereeta Y. (2014)
ZnMoO4 nanofibers were synthesized by electrospinning-calcination combinations. In the present research, anorthic structured ZnMoO4 was detected by X-ray diffraction (XRD) and confirmed by simulation and selected area electron diffraction (SAED). Morphology was confirmed by scanning and transmission electron microscopy (SEM, TEM) and atomic force microscopy (AFM). Vibrations were detected by Fourier transform infrared (FTIR) and Raman spectroscopy. By using photoluminescence (PL) and UV-visible spectroscopy, the PL emission was found to be in the same range as the indirect energy gap (Eg). A formation mechanism was proposed according to the experimental results. © 2011 Elsevier B.V.